1917 and All That: A History of Russian at Glasgow University. (2nd July 2017) - Dunn, John
ABSTRACT: This article examines the history of Russian teaching at Glasgow University from the beginning of 1917 up to the present day, paying particular attention to the context in which the original lectureship was created and to the period from 1976 onwards. Consideration is also given to the questions of who studied Russian, what they were taught and what links have existed with the Soviet Union and post-Soviet Russia.